PENGARUH RASIO PROFITABILITAS, RASIO LIKUIDITAS, DAN RASIO SOLVABILITAS TERHADAP HARGA SAHAM (Studi Empiris pada Sektor Transportasi dan Logistik yang terdaftar Di Bursa Efek Indonesia Periode 2019-2021) - Shandra Devi, Putri; Herinanto, Redy (LPPM STIE YKPN Yogyakarta, 2023)
This study aims to partially and simultaneously analyze the effect of profitability, liquidity, and solvency ratios on stock prices in the Transportation and Logistics sector listed on the Indonesia Stock Exchange for the 2019-2021 period. This research was conducted using quantitative methods and taken from secondary data in the form of company quarterly financial report data. The population in this study was 30 Transportation and Logistics companies listed on the Indonesia Stock Exchange and a sample taken of 10 companies. The results showed that partially current ratio (CR), debt to equity ratio (DER) has a negative and insignificant effect on stock prices, while return on equity (ROE) has a positive and insignificant effect on stock prices. Simultaneously, the current ratio, debt to equity ratio, and return on equity have no significant effect on the stock price.